The economic impact of the 2011 drought on southern Colorado: a combined input-output and EDMP analysis - Gunter, Allison, author; Goemans, Christopher, author; Pritchett, James, author; Thilmany, Dawn, author; Department of Agricultural and Resource Economics, Colorado State University, publisher (Colorado State University. Libraries, 2012)
Water is a critical input to agricultural activities. Water shortages reduce productivity leading to reductions in yields, harvestable acres and forage for livestock. Since October of 2010, extreme drought has plagued agricultural producers throughout much of Southern Colorado (U.S. Drought Monitor Archive, 2012). Given agriculture's prominent role as a base industry in rural regional economies, the impact of the 2011 drought extends well beyond lost revenues to those producers directly impacted. The primary objective of this research is to describe and quantify the broader economic impacts of the 2011 drought on agricultural productivity and allied economic activity for two Colorado watersheds: the Rio Grande and the Arkansas.
July 2012.
Keywords: Droughts -- Economic aspects -- Colorado; Crops -- Effect of drought on -- Colorado